Kepedulian Novis Sang Timur Dalam Berekologi Sebagai Ungkapan Iman Di Komunitas Bandulan Malang - Genoveva Jawa; Intansakti Pius X (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2024)
Starting from the reflections of the Sang Timur Novice Sisters in Bandulan Malang after undergoing faith deepening in the 2023 Development Fasting Action with the theme